Organization maintenance of health related physical culture work with students in out-of-school establishments - I.A. Kogut; V.L. Marynych (Physical Education of Students)
Purpose: to substantiate the ways of organization of health related physical culture work with students in establishments of additional education. Material: in the research 12 experts in physical culture and additional education participated. We carried out expert questioning, which included questions about reasons of negative tendencies in children’s health in educational system. Results: we substantiated the role of additional education establishments, as places of health related physical culture work with students, realization. Potential of additional education establishments is optimization of resources by the following criteria: level of organizational changes (regional); place of innovations’ implementation (educational establishment); place of innovations’ realization (content, forms, methods). Realization of the youth’s educational policy is possible on the base of all educational system’s links involvement in process of strengthening and improvement of every citizen’s health. Increase of youth’s motor functioning will permit to significantly shorten expenditures for health protection system. Conclusions: the ways of health related physical culture work with students’ organization are the following: students’ trainings in sports circles, in youth clubs and additional education establishments of physical culture-sports and health related orientation; organization of creative associations on the base of HEEs; promotion of circles of non-Olympic kinds of sports.